Protecting the Environment with Human Rights: Mechanism Rooted in Anthropocentric Approach - Habiba, Umma (Human Rights in the Global South (HRGS), 2023)
Anthropocentric and eco-centric are the two existing philosophical views on protecting the environment. The latter emphasises environmental protection for its intrinsic value, while the former is human-centred. This paper explores the relationship between promoting human rights and protecting the environment by arguing that the anthropocentric approach, which places humanity at its centre and is grounded in utilitarianism theory, can be a valuable tool in bridging these two areas. According to utilitarianism, achieving all fundamental human rights will contribute to raising environmental standards. Hitherto, the anthropocentric approach has been regarded to be only advantageous to humans, but in reality, it has a positive which mutually reinforces the effect on both the environment and humans. Humans will naturally turn their attention to environmental protection after they obtain all rights to meet a standard life. In the pursuit of environmental justice, humans will endeavour to improve their surroundings sustainably while upholding their fundamental rights. Through this relationship, a rights-based approach and environmental protection mechanisms are established, allowing individuals to seek redress for any kind of environmental harm as a distinct category of human rights. In conclusion, by establishing a distinct environmental-human right and tying it to human rights, environmental protection can be realised more practically.